ANALISIS STRATEGI PEMASARAN BERDASARKAN POSISI UMKM KOPI DI KAWASAN WISATA EDUKASI GOMBENGSARI KABUPATEN BANYUWANGI - Andiananta Pradana, Hendra; Novita, Elida; Ardiyan Savendra, Mico (Jurnal Riset Entrepreneurship, 2025)
The right marketing strategy has a positive impact on product sales, which in turn affects the income of Micro, Small and Medium Enterprises (MSMEs) producing coffee products in the Gombengsari Educational Tourism Area. The research aim to develop a marketing strategy for processed coffee products using the SWOT method and quadrant mapping of coffee product MSMEs in the Gombengsari Educational Tourism Area. The identification of internal factors, including strengths and weaknesses, as well as external factors, including opportunities and threats, was carried out on eight coffee product MSMEs. The marketing strategy was developed based on the quadrant position of MSMEs according to the results of the SWOT analysis. The development of marketing strategies also considered the results of quadrant mapping using a geographic information system. The SWOT analysis results showed that seven MSMEs is positioned in quadrant I and one MSMEs in quadrant IV. The recommended marketing strategies is participating in MSMEs exhibitions or events, strengthening networks with tourists, and digital marketing. The position mapping of MSMEs coffee products in five areas in Gombengsari Village show that almost all of them are located in quadrant I, which indicates that their positions in an aggressive status or have internal strengths in the form of resources or types of businesses that can of creating opportunities for business growth. The study can be used as a consideration in developing MSMEs marketing strategies combined with the provision of educational tourism services that have the potential to increase the income of the coffee farmer community.